2004
DOI: 10.1086/381438
|View full text |Cite
|
Sign up to set email alerts
|

AeromonasMeningitis Complicating Medicinal Leech Therapy

Abstract: Medicinal leeches have an important and expanding role in medicine, but infection can complicate their use. We describe a unique case of Aeromonas meningitis associated with the use of leech therapy to salvage a skin flap after central nervous system surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
29
0
6

Year Published

2004
2004
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(35 citation statements)
references
References 5 publications
0
29
0
6
Order By: Relevance
“…However, in a few instances, invasive disease has been reported. Aeromonas septicemia has been reported as a consequence of leech therapy in males suffering from crush injuries, accidental amputations, or plastic surgery related to malignancies (77,86,110) and has also seeded secondary infections of the central nervous system (CNS), such as meningitis (229). Most of the aeromonads recovered from such illnesses have been identified as A. veronii bv.…”
Section: Blood-borne Infectionsmentioning
confidence: 99%
“…However, in a few instances, invasive disease has been reported. Aeromonas septicemia has been reported as a consequence of leech therapy in males suffering from crush injuries, accidental amputations, or plastic surgery related to malignancies (77,86,110) and has also seeded secondary infections of the central nervous system (CNS), such as meningitis (229). Most of the aeromonads recovered from such illnesses have been identified as A. veronii bv.…”
Section: Blood-borne Infectionsmentioning
confidence: 99%
“…A. salmonicida is the causative agent of the fish disease called furunculosis but human disease has not been described (Isonhood and Drake, 2002). Ouderkirk et al (2004) described a case of meningitis caused by A. veronii biovar sobria associated with the use of leech therapy to salvage a skin flap a�er central nervous system surgery.…”
Section: Aeromonas Sppmentioning
confidence: 99%
“…The potential of the Aeromonas species to cause diseases in humans has been studied, but only recently a major number of clinical cases have been confirmed and attributed to these organisms (Clark & Chenoweth 2003;Vila et al 2003;Ouderkirk et al 2004;Pinna et al 2004;Martin-Carnahan & Joseph 2005;Hiransuthikul et al 2005;Daskalov 2006;Hofer et al 2006). Ribeiro et al (2010) Aeromonas species are the most common organisms reported in infections of burns exposed to contaminated water.…”
Section: Introductionmentioning
confidence: 99%